Sensitive multi-species photoacoustic gas detection based on mid-infrared supercontinuum source and miniature multipass cell. Issue 32 (5th August 2022) - Mikkonen, Tommi; Hieta, Tuomas; Genty, Goëry; Toivonen, Juha
Abstract : We demonstrate ppb-level hydrocarbon detection and the analysis of complex gas mixtures in a small sample volume using Fourier transform spectroscopy with cantilever-enhanced photoacoustic detection, a supercontinuum laser and a multipass cell. Abstract : We report multipass broadband photoacoustic spectroscopy of trace gases in the mid-infrared. The measurement principle of the sensor relies on supercontinuum-based Fourier transform photoacoustic spectroscopy (FT-PAS), in which a scanning interferometer modulates the intensity of a mid-infrared supercontinuum light source and a cantilever microphone is employed for sensitive photoacoustic detection. With a custom-built external Herriott cell, the supercontinuum beam propagates ten times through a miniature and acoustically non-resonant gas cell. The performance of the FT-PAS system is demonstrated by measuring the fundamental C–H stretch bands of various hydrocarbons. A noise equivalent detection limit of 11 ppb is obtained for methane (40 s averaging time, 15 μW cm −1 incident power spectral density, 4 cm −1 resolution), which is an improvement by a factor of 12 compared to the best previous FT-PAS systems. High linearity and good stability of the sensor provide reliable identification of individual species from a gas mixture with strong spectral overlap, laying the foundation for sensitive and selective multi-species detection in small sample volumes.